2019
DOI: 10.3390/ma12111767
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Cyclic Behaviour of Martensitic Steel with J2 Plasticity and Crystal Plasticity

Abstract: In order to capture the stress-strain response of metallic materials under cyclic loading, it is necessary to consider the cyclic hardening behaviour in the constitutive model. Among different cyclic hardening approaches available in the literature, the Chaboche model proves to be very efficient and convenient to model the kinematic hardening and ratcheting behaviour of materials observed during cyclic loading. The purpose of this study is to determine the material parameters of the Chaboche kinematic hardenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 49 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…In the present study, initially, three backstress terms, which comprise six unknowns, and isotropic softening with two unknown parameters are used, leading to a total of eight unknowns, which are identified by using an inverse modeling technique. Furthermore, an effort has been made to use only two backstress terms, which reduces the unknown terms to six with the almost same quality of results in our case [31]. Therefore, in this study, only the results of two backstress terms are shown.…”
Section: Materials Modelmentioning
confidence: 99%
“…In the present study, initially, three backstress terms, which comprise six unknowns, and isotropic softening with two unknown parameters are used, leading to a total of eight unknowns, which are identified by using an inverse modeling technique. Furthermore, an effort has been made to use only two backstress terms, which reduces the unknown terms to six with the almost same quality of results in our case [31]. Therefore, in this study, only the results of two backstress terms are shown.…”
Section: Materials Modelmentioning
confidence: 99%
“…In the present study, three backstress terms, which comprise six unknowns, and isotropic softening with two unknown parameters are used initially, leading to a total of eight unknowns which are identified by using an inverse modeling technique. Furthermore, an effort has been made to use only two backstress terms, which reduces the unknown terms to six with the almost same quality of results in our case [ 31 ]. Therefore, in this study, only the results of two backstress terms are shown.…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…In such macroscopic analyses, a variety of models, e.g. Prager, Ziegler, Johnson-Cook, Ohno-Wang, Frederick-Armstrong, and Chaboche ones are commonly applied (Buljak et al, 2021;Genna, 1993;Remache et al, 2020;Chen et al, 2005;Schäfer, 2019;Sajjad et al, 2019). Material processing analyses including only the macroscopic behaviour of materials under cyclic loading were tested by authors in the past.…”
Section: Introductionmentioning
confidence: 99%